APPLICATION OF MANAGEMENT TECHNOLOGIES DURING THE FORMATION OF AN INNOVATION DEVELOPMENT STRATEGY IN THE CONTEXT OF GLOBALISATION - SAKUN, Lesia; VIEDIENINA, Yuliia; SHYSHLOVA, Yuliia; PANCHENKO, Mariia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article discusses the essence of strategic enterprise development management and outlines the key aspects of using management technologies in formation of an innovative development strategy in the conditions of an unstable market and globalization. It has been identified that managing weak and strong signals is a modern tool to enhance the efficiency of enterprise activities amidst uncertainty and changes in the external environment. The procedure for organizational actions in the case of weak signals regarding emerging problems is defined, and the main aspects of successful management of strong and weak signals in the enterprise are indicated. Diagnostics of the internal and external environment and assessment of the overall strategy for PrJSC "Kredmash" were carried out. The analysis of the issuer’s financial condition included the coefficients of economic stability and resource potential, which illustrate the negative trend and significant impact of the war consequences on the enterprise’s activities, and the results of the calculations revealed that 70% of own funds are used to finance the current activities of PrJSC "Kredmash". SWOT-analysis and PEST-analysis made it clear to what extent the company can overcome weaknesses with the help of opportunities, and which environmental factors have the most significant impact on its activities. A series of solutions based on SWOT analysis were also proposed for the further development and optimization of the machinery manufacturing enterprise’s activities. A proposed strategy for the development of machine-building enterprises (in particular, the researched PrJSC "Kredmash") has been formed along with an action plan regarding the implementation of the strategy in the current conditions of functioning.